Digitally Tunable Microfluidic Bioprinting of Multilayered Cannular Tissues - Pi, Qingmeng; Maharjan, Sushila; Yan, Xiang; Liu, Xiao; Singh, Bijay; Genderen, Anne Metje; Robledo‐Padilla, Felipe; Parra‐Saldivar, Roberto; Hu, Ning; Jia, Weitao; Xu, Changliang; Kang, Jian; et al. (Advanced materials (Weinheim), 2018)
Despite advances in the bioprinting technology, biofabrication of circumferentially multilayered tubular tissues or organs with cellular heterogeneity, such as blood vessels, trachea, intestine, colon, ureter, and urethra, remains a challenge. Herein, a promising multichannel coaxial extrusion system (MCCES) for microfluidic bioprinting of circumferentially multilayered tubular tissues in a single step, using customized bioinks constituting gelatin methacryloyl, alginate, and eight‐arm poly(ethylene glycol) acrylate with a tripentaerythritol core, is presented. These perfusable cannular constructs can be continuously tuned up from monolayer to triple layers at regular intervals across the length of a bioprinted tube. Using customized bioink and MCCES, bioprinting of several tubular tissue constructs using relevant cell types with adequate biofunctionality including cell viability, proliferation, and differentiation is demonstrated. Specifically, cannular urothelial tissue constructs are bioprinted, using human urothelial cells and human bladder smooth muscle cells, as well as vascular tissue constructs, using human umbilical vein endothelial cells and human smooth muscle cells. These bioprinted cannular tissues can be actively perfused with fluids and nutrients to promote growth and proliferation of the embedded cell types. The fabrication of such tunable and perfusable circumferentially multilayered tissues represents a fundamental step toward creating human cannular tissues. A multichannel coaxial extrusion system for microfluidic bioprinting of circumferentially multilayered tubular tissues is presented. The fabrication of such tunable and perfusable circumferentially multilayered tissues represents a fundamental step toward creating human cannular tissues.